Pengaruh Struktur Modal Dan Ukuran Perusahaan Terhadap Kinerja Keuangan Dengan Good Corporate Governance Sebagai Variabel Moderasi ( studi pada Perusahaan Manufaktur industri Pariwisata dan Rekreasi yang terdaftar di Bursa Efek Indonesia tahun 2020 – 2022 - Dian Aulia Putri; Ratnawati raflis (CV. ITTC INDONESIA, 2024)
This research aims to examine the influence of capital structure and company size on financial performance which is moderated by good corporate governance in tourism and recreation industry manufacturing companies listed on the Indonesia Stock Exchange in 2020 - 2022. In this research the method used is quantitative using data secondary, the sample was taken using purposive sampling and 40 companies were obtained that met the sample determination criteria. The technique used in this research is multiple linear regression analysis and MRA analysis using SPPS version 21. The results of this research show 1). Capital structure has a positive and significant effect on financial performance. 2) Company size has no significant effect on financial performance. 3) Good corporate governance is able to moderate positively and significantly the influence of capital structure on financial performance. 4) Good corporate governance is not able to moderate the influence of company size on financial performance.